Techno-Economic Aspect of Dimension Stone Mining In Chitral, Khyber Pakhtunkhwa: Techno-Economic Aspect of Dimension Stone Mining In Chitral, Khyber Pakhtunkhwa - Din Khan, Ihsanud; Ur Rehman, Safi; Hassan, Umair (International Journal of Economic and Environmental Geology, 2023)
In developing countries like Pakistan which are bestowed by nature with huge deposits of minerals are largely run by small scale mining, and mostly result in wasting precious deposits by adopting conventional mining methods neglecting the health and safety aspect. This research endeavour analyzed the techno-economic aspects of various mining methods for extraction of dimension stone in chitral region and proposed a suitable mining method based on these aspects. Seven different deposits of dimension stone were taken as case studies to evaluate the proposed approach. For each deposit, twelve criteria were compared as per the procedure of Analytical Hierarchy Process (AHP). These aspects are quality, quantity, mining cost, infrastructure, mining and processing losses, mining time, equipment’s performance, skilled labour, work capacity to fragment the deposits, benching and safety. Whereas, the alternatives are mechanized mining, material expansion/controlled blasting and conventional mining. The criteria were compared and methods suitable for each deposit were suggested. Keywords: Dimension stone, small scale mining, marble quarrying, dimension stone, analytical hierarchy process.